2014
DOI: 10.1182/blood-2014-04-568436
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant in folate homeostasis is associated with lower warfarin dose in African Americans

Abstract: Key Points• A population-specific genetic variant involved in folate homeostasis is associated with lower warfarin dose in African Americans.The anticoagulant warfarin has >30 million prescriptions per year in the United States. Doses can vary 20-fold between patients, and incorrect dosing can result in serious adverse events. Variation in warfarin pharmacokinetic and pharmacodynamic genes, such as CYP2C9 and VKORC1, do not fully explain the dose variability in African Americans.To identify additional genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…First, a GWAS in African-Americans showed that a SNP in the CYP2C gene cluster (rs12777823) independently of CYP2C9*2 and CYP2C9*3 also influenced warfarin dose requirement, improving the variability explained by the IWPC algorithm by 21% [43]. Second, an exome sequencing study in African-American patients on extremes of doses showed that individuals with a variant allele in folylpolyglutamate synthase (FPGS) (rs7856096) required lower doses [44]. Consistent with this, an ethnicity-specific algorithm performed better than the original IWPC algorithm in a recent study [45].…”
Section: Ethnic Heterogeneitymentioning
confidence: 98%
“…First, a GWAS in African-Americans showed that a SNP in the CYP2C gene cluster (rs12777823) independently of CYP2C9*2 and CYP2C9*3 also influenced warfarin dose requirement, improving the variability explained by the IWPC algorithm by 21% [43]. Second, an exome sequencing study in African-American patients on extremes of doses showed that individuals with a variant allele in folylpolyglutamate synthase (FPGS) (rs7856096) required lower doses [44]. Consistent with this, an ethnicity-specific algorithm performed better than the original IWPC algorithm in a recent study [45].…”
Section: Ethnic Heterogeneitymentioning
confidence: 98%
“…7 There are also variants important for dosing among individuals of African descent alleles that were unaccounted for in these trials. 711 Drozda found that failing to take into account these expanded variants resulted in significantly worse dose predictions among African Americans. 12 Additionally, Limdi found that using a race stratified dosing approach resulted in significantly more dose variation explained in both whites and blacks compared to a race-combined dosing model.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the advent of more-expensive, ‘next-generation’ sequencing technology, extreme drug-response phenotypes—defined typically as those individuals with drug response ≤5 th percentile, or ≥95 th percentile—are more commonly used to identify novel pharmacogenetic markers (for example, in warfarin dosing). 18 …”
Section: Identifying Pharmacogenetic Markersmentioning
confidence: 99%